ANALISIS SPASIAL AREA SEBARAN KEBAKARAN HUTAN DI KABUPATEN TEBO 2015 – 2025 - Resita Paradina; Elvi Zuriyani; Rika Despica (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Forest fires are one of the environmental problems that often occur and areconsidered important so that they become local and global concerns. Forest firesare an event that often occurs in Indonesia. Climate is one of the natural factorsthat can support the occurrence of forest fires, because climate conditions canaffect the level of dryness of settlement materials. The purpose of this study is toanalyze the spatial distribution of forest fires in Tebo Regency 2015-2025. Thedata used in this study are hotspots using Modified Sentinel 2024 imagery, firearea data. The results of the study show that in 12 sub-districts in Tebo Regency,Muara Tabir Sub-district is the area with the most fires with 5 hotspots, the factorscausing forest fires in Tebo Regency are natural factors and human factors.